The Origins of Gun Policy in U.S. States - Geoff Dancy; Mirya Holman; Kayden McKenzie (Washington University Journal of Law & Policy, 2019)
This article examines gun regulation at the state level. It argues that, while federal gun regulation remains quite rare, the states frequently act in the gun regulation arena. From a political geography perspective, this article examines the attitudes underlying state-level gun regulation measures. To do so, the article draws on a dataset of over 4,700 gun-related bills introduced in state legislatures between 2011 and 2015. This analysis yields the conclusion that areas with higher crime rates are less likely to support gun rights legislation, while rural areas and those with a higher proportion of white residents, are more likely to support such bills.
Keywords: gun policy; gun regulation; state; federal; political geography; state legislature; bills; legislation